Serum Amyloid A as a Surrogate Marker for Mucosal and Histologic Inflammation in Patients with Crohn's Disease. Issue 1 (January 2017) - Yarur, Andres J.; Quintero, Maria A.; Jain, Anjali; Czul, Frank; Barkin, Jamie S.; Abreu, Maria T.
Abstract : Background: Serum amyloid A (SAA) is an acute-phase protein, but its role as a biomarker of disease activity in Crohn's disease is unclear. The aim of the study was to assess the correlation between SAA, inflammatory cytokines, and mucosal inflammation in patients with Crohn's disease and to investigate whether this marker might be useful in patients who do not have elevated C-reactive protein (CRP) levels despite having active disease. Methods: Cross-sectional study including patients with Crohn's disease who underwent colonoscopies for assessment of disease activity. Predictive variables were recorded at the time of the procedure and included demographics, phenotype of disease, medications, and collection of serum for cytokine analysis (SAA, CRP, intercellular adhesion molecule-1, vascular cell adhesion molecule-1, and interleukins 8, 1β, and 6). The primary outcome was the presence of mucosal healing (MH) (absence of macroscopic and microscopic inflammation). Results: Ninety-four patients were included. Sixty-eight (72.3%) had not achieved MH. SAA, CRP, intercellular adhesion molecule, and interleukin-6 levels were significantly lower in those patients with MH. SAA was the only test that performed well in the sensitivity/specificity analysis (receiver operating characteristic: 0.81, P = 0.046). A high SAA was able to identify 70% of the patients with a normal CRP but active inflammation. Conclusions: High circulating SAA levels can correlate with lack of MH and may be used as a surrogate marker for disease activity, even in those patients in whom CRP levels do not correlate with disease activity. Abstract : Article first published online 7 December 2016.